The Strength and Drivers of Bird-Mediated Selection on Fruit Crop Size: A Meta-Analysis - Palacio, Facundo X.; Ordano, Mariano (Frontiers in Ecology and Evolution, 2018)
In seed-dispersal mutualisms, the number of fruit a plant displays is a key trait, as it acts as a signal for seed dispersers that entails fruit removal and exportation of reproductive units (fruit crop size hypothesis). Although this hypothesis has gained general acceptance, forces driving the shape and strength of natural selection exerted by birds on fruit crop size remains an unresolved matter. Here, we propose that ecological filters promoting high functional equivalence of interacting partners (similar functional roles) translate into similar selection pressures on fruit crop size, enhancing selection strength on this trait. We performed a meta-analysis on 50 seed-dispersal systems to test the hypothesis that frugivorous birds exert positive selection pressure on fruit crop size, and to assess whether different factors expected to act as filters (fruit diameter, fruit type, fruiting season length, bird functional groups and latitude) influence phenotypic selection regimes on this trait. Birds promote larger fruit crop sizes as a general pattern in nature. Short fruiting seasons and a high proportion of species belonging to the same functional group showed higher selection strength on fruit crop size. Also, selection strength on fruit crop size increased for large-fruited species and towards the tropics. Our results support the hypothesis that fruit crop size represents a conspicuous signal advertising the amount of reward to visually driven interacting partners, and that both plant and bird traits, as well as environmental factors, drive selection strength on fruit display traits. Furthermore, our results suggest that the relationship among forces impinged by phenology and frugivore functional roles may be key to understand their evolutionary stability.